β-Glucan reduces cortisol plasma levels, enhances innate immune system after A. hydrophila inoculation, and has lipolytic effects on the pacu (Piaractus mesopotamicus) - Lopes, Larissa Maria Frazão [UNESP]; Mello, Mariana Maluli Marinho de [UNESP]; Urbinati, Elisabeth Criscuolo [UNESP] (Elsevier, 2022)
Although β-glucan is a compound widely used to enhance innate immunity in fish, very little is known about its metabolic effects as described in humans and other animals. This study evaluated the effects of dietary β-glucan from Saccharomyces cerevisiae on stress, innate immune and metabolic responses in the pacu (Piaractus mesopotamicus) juveniles. The fish (85.2 ± 24.8 g) were subjected to the following treatments: a) commercial feed CF (0% β-glucan – control); b) CF supplemented with 0.1% β-glucan, and c) CF supplemented with 0.5% β-glucan (eight 130 L tanks/treatment, 72 fish per treatment). The fish were sampled after 15 days of β-glucan administration (basal sampling) to assess the metabolic responses (lipid levels in blood and tissues) and then inoculated with heat-inactivated A. hydrophila to assess the stress and immune responses. For the first time, β-glucan showed a modulatory effect on lipid metabolism in fish. We found a reduction in plasma triglyceride levels, as also in lipid levels in liver, muscle, and visceral depots, in fish fed with β-glucan. The triglyceride levels decreased by 32.9% in fish fed with 0.1% β-glucan, when compared to the control group. Lipid levels decreased by 42.8% and 26.8% in the liver, and by 37.9% and 24.1% in muscle, for fish fed with 0.1% and 0.5% β-glucan, respectively, compared to the control group. Visceral fat decreased by 32.1% and 46.4%, in fish fed with 0.1% and 0.5% β-glucan, respectively. In addition to the lipolytic effect, β-glucan modulated cortisol profile reducing the levels at rest and after inoculation with A. hydrophila bacterin, thereby confirming its immunostimulating action, by increasing the respiratory activity of leukocytes and lysozyme levels 24 h after inoculation. Our results show that, in addition to the immunostimulating action and cortisol reducer effect of the yeast-derived β-glucan, its lipolytic effect is quite promising, as the pacu is considered a fat fish in the market size and a leaner product would bring better features for the consumer.
Keywords: Bacterin inoculation; Innate immunity; Lipid depots; Lipid metabolism; Stress